2019
DOI: 10.1039/c9ta03249e
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the water dissociation kinetics of Ni3N nanosheets via in situ interfacial engineering

Abstract: The sluggish water dissociation kinetics of Ni3N is significantly accelerated by in situ interfacial engineering. Owing to the unique synergy between Ni3N and MoO2, Ni3N/MoO2 displays exceptional alkaline HER activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…Unlike alloying, which typically alloys metallic materials with one or more other metals, heterostructure engineering involves the hybridization of different categories of NS compounds with interfaces, such as sulfides and selenides, [ 114 ] sulfides, [ 115 ] nitrides, [ 116 ] carbides and nitrides, [ 117 ] thiophosphates and phosphides. [ 118 ] Taking advantage of the synergetic chemical coupling effects (e.g., modified electronic state and advantageous physical and chemical properties) between different interfaces, heterostructure‐engineered catalysts are expected to present excellent electrochemical performance for electrocatalytic applications.…”
Section: Electronic Structure Engineering Of Non‐vdw 2d Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike alloying, which typically alloys metallic materials with one or more other metals, heterostructure engineering involves the hybridization of different categories of NS compounds with interfaces, such as sulfides and selenides, [ 114 ] sulfides, [ 115 ] nitrides, [ 116 ] carbides and nitrides, [ 117 ] thiophosphates and phosphides. [ 118 ] Taking advantage of the synergetic chemical coupling effects (e.g., modified electronic state and advantageous physical and chemical properties) between different interfaces, heterostructure‐engineered catalysts are expected to present excellent electrochemical performance for electrocatalytic applications.…”
Section: Electronic Structure Engineering Of Non‐vdw 2d Materialsmentioning
confidence: 99%
“…Recently, researchers have demonstrated that non‐vdW 2D materials, including metal alloys (based on Ni, Fe, Co, Mo, etc. ), [ 106,146 ] metal chalcogenides, [ 57,92,114,115,147,148 ] metal nitrides, [ 81,91,116,149,150 ] and metal carbides/phosphides, [ 69,82,96,133–136,151 ] present remarkable properties for the electrocatalytic HER owing to unique structural and electronic properties. For example, ultrathin 2D Ni–Mo alloy NSs were deposited on a Ni foam substrate and were used as HER catalysts.…”
Section: Non‐vdw 2d Materials For Electrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental efforts have shown that substitutional doping of Ni with other transition metals could vastly improve HER activity by providing alternative hydrogen adsorption sites to the (001) surface [49][50][51]. The formation of heterostructures by coupling Ni 3 N with other materials, such as transition metal oxides [52,53] or nitrides [54,55], have also shown great promise. A NiMoN/Ni 3 N heterostructure synthesized by Wang et al [55] was demonstrated to exhibit an extremely low overpotential of 28 mV at 10 mA cm −2 , owing to the synergistic effect between the two materials that favoured charge transfer processes for water dissociation.…”
Section: Hydrogen Adsorption To Ni 3 N Surfacesmentioning
confidence: 99%
“…In this regard, it is highly imperative to develop Earthabundant and cost-effective but efficient HER catalysts to replace precious Pt. Examples of these non-precious electrocatalysts include transition metal chalcogenides [4][5][6], carbides [7,8], nitrides [9][10][11], and phosphides [12][13][14]. Among these available HER electrocatalyst candidates, two-dimensional transition metal chalcogenides (2D-TMCs), such as MoS 2 , WS 2 , MoSe 2 , and WSe 2 , have attracted substantial interest due to their low cost, large specific surface area, high atomic exposure, tunable electronic structure, and high intrinsic per-site HER activity [4,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%